Automated Layer-by-Layer Soil Tillage Machine Using a Highly Turbulent Air Jet - B. Kh. Akhalaya; Yu. S. Tsench; N. I. Belyaeva (Сельскохозяйственные машины и технологии, 2025)
The paper highlights that preserving and enhancing the soil fertility of agricultural lands remains one of the most pressing challenges for the national economy. In soil conservation farming systems, no-till soil cultivation plays a crucial role in preventing wind and water erosion, regulating the soil’s physical, chemical, and biological properties, and optimizing the use of soil and climatic resources to ensure higher and more stable crop yields. (Research purpose) To develop an automated layer-by-layer soil tillage machine that utilizes a highly turbulent air jet to improve soil fertility and reduce the traction resistance of the machine-tractor unit. (Materials and methods) A design was developed for an automated layer-by-layer soil tillage machine utilizing a highly turbulent air jet. Upon receiving a signal from the control system, pneumatic solenoid valves are activated supplying compressed air to the working tools. The machine is equipped with needle rollers having needles up to 10 centimeters long and disc mills capable of reaching tillage depths of 15–20 centimeters for root crops and 8–12 centimeters for grain crops. The working tools include two arc-shaped blades arranged in sequence with a spacing of 15–20 centimeters; the front blade operates at a depth of 10–12 centimeters, while the rear blade is positioned 10–12 centimeters lower to enable multi-layer soil tillage. (Results and discussion) The results demonstrate that the proposed design delivers impulse bursts of compressed air that loosens the soil without disturbing its structure. This improves operational efficiency and supports both continuous and row-specific tillage. Moreover, the system enhances quality indicators and reduces fuel consumption. (Conclusions) The development of an automated layer-by-layer soil tillage machine utilizing a highly turbulent air jet offers a promising solution for preserving and improving soil fertility.